2022
DOI: 10.3390/ijms232012311
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Long COVID-19 Management: From Disease Molecular Hallmarks to the Proposal of Exercise as Therapy

Abstract: Long coronavirus disease 19 (COVID-19) is the designation given to a novel syndrome that develops within a few months after infection by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and that is presenting with increasing incidence because of the numerous cases of infection. Long COVID-19 is characterized by a sequela of clinical symptoms that concern different organs and tissues, from nervous, respiratory, gastrointestinal, and renal systems to skeletal muscle and cardiovascular apparatus. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…For their part, Scurati et al found in their own review that exercise is known to exert a deep action on molecular dysfunctions elicited by long COVID-19. Of course, it depends on training, intensity, duration and continuity, but the information they presented bears the consideration of properly regulated exercise as part of the management protocol for long COVID [ 239 ]. For patients exhibiting the fatigue or post-exertional malaise characteristic of both long COVID and ME/CSF, a personalized, symptom-guided program for a phased return to activity is recommended [ 230 ].…”
Section: Treatment: Targeting Latent Viral Reactivation and Microbiot...mentioning
confidence: 99%
“…For their part, Scurati et al found in their own review that exercise is known to exert a deep action on molecular dysfunctions elicited by long COVID-19. Of course, it depends on training, intensity, duration and continuity, but the information they presented bears the consideration of properly regulated exercise as part of the management protocol for long COVID [ 239 ]. For patients exhibiting the fatigue or post-exertional malaise characteristic of both long COVID and ME/CSF, a personalized, symptom-guided program for a phased return to activity is recommended [ 230 ].…”
Section: Treatment: Targeting Latent Viral Reactivation and Microbiot...mentioning
confidence: 99%
“…Regarding the management of symptoms, existing evidence is limited to exercise training rehabilitation, which improved dyspnea in Long COVID ( 42 ). Initial research mainly focused on symptom-centered treatments that included naltrexone against neuro-inflammation, beta blockers for postural tachycardia syndrome, antihistamines and/or intravenous immunoglobulins for immune dysfunction and cognitive pacing for cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The study population includes studies with adults (18 years or older) diagnosed with long COVID‐19, defined as the continuation or development of new symptoms 3 months after the initial SARS‐CoV‐2 infection (Scurati et al., 2022). Studies with acute or subacute populations were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, a consistent percentage of patients affected by COVID‐19 continue with symptoms after the acute phase. This new disease is known as Long COVID‐19 (LC) and was defined by the World Health Organization as “the continuation or development of new symptoms 3 months after the initial SARS‐CoV‐2 infection” (Scurati et al., 2022), and potentially affects from 10% to 50% of patients (Bouteleux et al., 2021). Due to multiorgan involvement in LC cases, breathlessness, fatigue, neuropsychological symptoms, cough, musculoskeletal pain, and alterations in smell and taste were the most commonly associated symptoms (Jimeno‐Almazán et al., 2021; Scurati et al., 2022).…”
Section: Introductionmentioning
confidence: 99%